Use of a non-medicated tape in non-specific low back pain: A single-blind, randomized, placebo-controlled trial - Lavagnolo, Umberto; Ricci, Matteo; Cason, Mattia; Vecchini, Eugenio; Maluta, Tommaso; Bertinato, Chiara; Sartori, Sabrina (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Low back pain (LBP) is prevalent and often non-specific disease. Kinesiology taping shows mixed evidence, and far-infrared (FIR)–reflecting tapes are promising. To evaluate the efficacy of an FIR-reflecting tape (FT) versus standard kinesiology tape (KT) and placebo for chronic non-specific LBP.Methods: A single-blind trias was conducted evaluating adults patients (aged 30–60 years) with chronic LBP >6 months, NRS 6–10, no radiculopathy or red flags; n=240 randomized (FT, n=80; KT, n=80; placebo, n=80). Tapes were applied to the lumbar region for two 5-day applications separated by a 3-day interval (total 14 days). Outcomes at T0, T1 (day 5), T2 (day 8), and T3 (day 14) included pain (NRS), disability (Roland-Morris Disability Questionnaire, RMDQ), and lumbar range of motion (ROM). Non-parametric analyses (Shapiro–Wilk; Kruskal–Wallis; Friedman) with α=0.05.Results: All participants completed the protocol with no adverse events. Groups were comparable at baseline. Between-group differences favored FT at all post-baseline time points for NRS, RMDQ, and ROM (p